2017
DOI: 10.5194/acp-2017-694
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Aerosol characteristics and particle production in the upper troposphere over the Amazon Basin

Abstract: <p><strong>Abstract.</strong> Airborne observations over the Amazon Basin showed high aerosol particle concentrations in the upper troposphere (UT) between 8 and 15 km altitude, with number densities (normalized to standard temperature and pressure) often exceeding those in the planetary boundary layer (PBL) by one or two orders of magnitude. The measurements were made during the German-Brazilian cooperative aircraft campaign ACRIDICON-CHUVA on the German… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
10
0
3

Year Published

2018
2018
2019
2019

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 131 publications
5
10
0
3
Order By: Relevance
“…These climatological streamlines are derived from a reanalysis of the period from 1981 to 2010. As shown in Andreae et al (2017), similar wind patterns were found during the AC campaign in September 2014. LT winds over the Amazon Basin are strongly influenced by the Andes mountain range (Campetella & Vera, 2002).…”
Section: Lower Tropospheresupporting
confidence: 77%
“…These climatological streamlines are derived from a reanalysis of the period from 1981 to 2010. As shown in Andreae et al (2017), similar wind patterns were found during the AC campaign in September 2014. LT winds over the Amazon Basin are strongly influenced by the Andes mountain range (Campetella & Vera, 2002).…”
Section: Lower Tropospheresupporting
confidence: 77%
“…Therefore, the cloud droplet size distribution is different between the two regions, with forested areas producing larger cloud droplets. Figure 12 shows the cumulative histogram of the CCN concentrations (N CCN ) for the two legs over the forested and non-forested regions at approximately 1500, 1900, and 2500 m. The decrease in N CCN with altitude for boundary layer aerosols agrees with the other flights carried out during the ACRIDICON-CHUVA campaign, as shown in Andreae et al (2017). The magnitude of the N CCN is typical for polluted regions in Brazil and falls between strong biomass burning events and forested regions far away from biomass burning events.…”
Section: Rainfall Sensitivity To Surface Coversupporting
confidence: 72%
“…Water droplets with a diameter ≥ 1 µm were detected by an optical particle counter. Details about the measurement mode can be found in Andreae et al (2017). The error in supersaturation resulted from the calibration uncertainty, as described by Pöhlker et al (2016); it is estimated to be in the range of 10 %.…”
Section: Methodsmentioning
confidence: 99%
“…Laakso et al (2007) also observed NPF in the mixed boundary layer and free troposphere in southern Finland using measurements on board a hot air balloon. The rapid downward mixing of small aerosol particles from the free troposphere represents an important source of aerosol particles in the pristine Amazon boundary layer (Wang et al, 2016;Andreae et al, 2017). Helicopter (Kupiszewski et al, 2013) and aircraft (Burkart et al, 2017) measurements of vertical profiles of aerosol particles in the summertime Arctic observed particle formation in the near-surface layer, with much lower concentrations at higher altitudes.…”
Section: Introductionmentioning
confidence: 99%